THE ROLE OF BUTTERFLIES TOWARDS CREATING ECOLOGICAL BALANCE AND BIODIVERSITY CONSERVATION IN SOUTHERN PART OF WESTERN GHATS (PALANI HILLS) - RAJA, J. DINESH; YASMIN, J. JAINUL; PRIYADHARSHINI, A. MELBA; ATHIF, P.; BUKHARI, A. SADIQ; MOHAMED, H. E. SYED (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
In Southern Part of Western Ghats (Tamilnadu), four tropical habitats with different disturbance levels were monitored for diversity and seasonal patterns in the community of butterfly species. Species richness occurred highest in late monsoon and early in winter. Majority of the butterfly species also showed abundance peaks in these seasons. Pollution and Climatic factors played a vital role in determining species composition in the afflicted areas and affected flight periods of some species but did not affect species richness. Loss of Biodiversity had a major impact on species composition and it favored only those Lycaenids and Nymphalids whose caterpillars feed on herbs. In case of one of the sites where phenophases of the larval food plant and population trend of a small Lycaenid was documented, the population showed rapid increase at the time when the plants were in suitable phenophase for growth of the caterpillars. A possible evolutionary interaction between herb-feeding and non-herb-feeding Lycaenids is proposed.